2007
DOI: 10.1590/s0100-84042007000400002
|View full text |Cite
|
Sign up to set email alerts
|

Rock outcrop vegetation in Brazil: a brief overview

Abstract: -(Rock outcrop vegetation in Brazil: a brief overview). This paper overviews the special issue of the Brazilian Journal of Botany dedicated to "Rock outcrop vegetation in Brazil". The main topics covered by this issue are phytogeography and vegetation ecology, plant life on shallow soils, plant reproduction and auto-ecology, morpho-physiology and plant adaptation, and finally conservation and global change. This collection of studies, in addition to other recent publications on Brazilian rocky outcrop vegetati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
19

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 52 publications
(72 reference statements)
0
21
0
19
Order By: Relevance
“…Cerca de 30% do total de espécies amostradas pertencem ao grupo de monocotiledôneas, como registrado em diversos afloramentos rochosos , Scarano 2007. A presença marcante deste grupo de plantas em afloramentos rochosos denomina, inclusive, um tipo de habitat, as touceiras de monocotiledôneas ("monocotyledonous mats") (Porembski et al 1997, Porembski 2007.…”
Section: Discussionunclassified
“…Cerca de 30% do total de espécies amostradas pertencem ao grupo de monocotiledôneas, como registrado em diversos afloramentos rochosos , Scarano 2007. A presença marcante deste grupo de plantas em afloramentos rochosos denomina, inclusive, um tipo de habitat, as touceiras de monocotiledôneas ("monocotyledonous mats") (Porembski et al 1997, Porembski 2007.…”
Section: Discussionunclassified
“…The rock outcrops of these ancient Banded iron formation (BIF) ranges are isolated xeric islands within a more mesic matrix. The communities are edaphically controlled and share many similarities with well studied xeric communities of granite/gneiss domes (inselbergs) commonly found both in tropical alpine areas of Africa and South America and the Mediterranean climate areas of South Western Australia (Hopper et al 1997;Porembski 2007;Scarano 2007;Yates et al 2007). Initial surveys of BIF ranges in South Western Australia have discovered a significant number of plant species new to science and identified species endemic to, or with distributions centered on, these ranges (Butcher 2007;Gibson et al 2007).…”
Section: Introductionmentioning
confidence: 87%
“…Normally, at lower pH, phosphorus (a critical element in the development of the vegetation (Sarmiento 1984)) precipitates, for example, with aluminum, and becomes less available to plants. However, in the stony grasslands we studied, it was found that during the dry season, soil pH decreased while phosphorus concentrations increased in what may be related to a reduction in the loss of mineral nutrients due to the absence of rainfall (Sarmiento 1984). The extreme abiotic conditions of the campos rupestres have strong consequences in terms of plant adaptation to constrained environmental conditions.…”
Section: Plant Communities Linked To Soil Composition and Structurementioning
confidence: 99%